Propiedades volumétricas y viscosimétricas de las mezclas binarias de N,N- Dimetilformamida + 1-pentanol a varias temperaturas - Páez, Francsisco J.; Páez, Manuel S.; Lans , Edineldo (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
Densities and viscosities of the binary mixtures of N,N-Dimethylformamide (DMF) + 1-pentanol were determined in the entire concentration interval at the following temperatures: (283,15, 288,15, 293,15, 298,15 y 313,15) K using an vibrating tube densimeter Anton Paar DMA 5000 and an viscosimeter Anton Paar AMVn respectively. The excess molar volumes , viscosity deviations , B viscosity coefficients and parameters of viscous flow activation were calculated. The effects of 1-pentanol concentration and temperature on parameters mentioned above were discussed. The results were interpreted in terms of the solute-solvent interactions in organic medias. The excess molar volumes were negative, which can mainly be explained by factors such as the solute-solvent intermolecular attractive forces as hydrogen bonding interactions, other weaker physical interactions as dipole forces, and any other similar forces; as well as the rearrange of the alcohol molecules into the spaces of the DMF ones. The viscosity deviations were high and negatives and increased with temperature in the entire concentration interval, what could indicate the presence of specific interactions between 1-pentanol and DMF molecules, the high negative values can specifically be interpreted considering the hydrogen bonding interactions in addition to the form and size of the studied molecules.